ผลของโปรแกรมการเรียนรู้แบบบูรณาการในการจัดการภัยพิบัติและอุบัติภัยหมู่ต่อสมรรถนะของทหารกองประจำการ: กรณีศึกษา มณฑลทหารบกที่ 21 จังหวัดนครราชสีมา - วีรยุทธ หมื่นบุญมี (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study used a quasi-experimental research design through One-group Pretest-posttest Design.The objectives of this study were to investigate capacity of enlisted soldiers after implementing an integrated program for disaster management and mass causality incident and to compare their capacity between pre- andpost-implementation of an integrated program for disaster management and mass causality incident. The sample was40 enlisted soldiers of the 21st Military Circle in Nakhon Ratchasima Province, selected by a purposive samplingto participate in the foresaid program. The research tools consisted of 1) Questionnaire as a tool for data collection,2) tools for conducting experiment, namely: 2.1) Assessment form for capacity of enlisted soldiers with a reliabilityof .077, and 2.2) The integrated program for disaster management and mass causality incident, and 3) Pre-test andPost-test as tools for experiment supervision with a reliability of .91. Data were analyzed using statistics including percentage, mean, standard deviation. and t-test.The results of the research could be concluded as follows:1. A mean score of capacity of enlisted soldiers after implementing an integrated program for disaster management and mass causality incident was higher than a mean score at pre-implementation with a statistical significance level of .05. Capacity score of enlisted soldiers at post-implementation was at a high level.2. A mean score of capacity of enlisted soldiers before implementing an integrated program for disaster management and mass causality incident was 25.15, which was at a low level. A mean score at post-implementationwas 45.08, which was at a high level. When mean score of capacity at post-implementation was higher than thatat pre-implementation with a statistical significance level of .05.The findings implied that the developed integrated program for disaster management and mass causality incident could enhance capacity of enlisted soldiers as reflected by a mean score of capacity at post-implementation was higher than before.